Steps toward community health promotion: Application of transtheoretical model to predict stage transition regarding smoking - Maryam Emadzadeh; Veda Vakili (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Recently, the Iranian Ministry of Health estimated about 750,000 deaths are attributed smoking complications. The aim of this study was to apply the transtheoretical model (TTM) on general population of Mashhad city to evaluate the stages of change and possible cultural factors regarding smoking cessation. METHODS: This descriptive, cross-sectional population-based study was conducted in Mashhad, Iran. A total number of 562 participants selected by multistage sampling. They were asked about stages of change for smoking cessation for both hookah and cigarette smoking. Stages of change refer to an orderly sequence of changes in smoking behavior that people progress through according to the TTM. Its six stages are as follows: precontemplation (PC) (no intention to quit smoking within 6 months), contemplation (planning to quit smoking in the following 6 months), preparation (planning to stop smoking within 1 month), action (quit smoking for <6 months), maintenance (stopped smoking for 6 months or more), and termination (will never smoke again). Data were analyzed using tests such as Chi-square, Kruskal-Wallis, and logistic regression by SPSS 11.5. RESULTS: About 18% and 19% of people in this study were regular hookah and cigarette smokers, respectively. There was significant difference between cigarette smoking and sex (P < 0.001) and marital status (P = 0.01). There was a statistically significant difference between stages of change in men and women from the point of cigarette smoking (P < 0.001). Male sex, hookah smoking, and alcohol abuse were predictors of PC, and age was the only predictor of termination stage for cigarette smoking. Sex did not have any role in hookah smoking. CONCLUSION: Targeted education based on gender and marital status warrant attention. Community-wide education and interventions such as increasing the price of cigarettes are desired.